Strategi Komunikasi Internal Berbasis Digital melalui Viva Engage dalam Corporate Event Kemerdekaan : Studi pada Perusahaan Energi Multinational (Jurnal Sosial Humaniora dan Pendidikan, 2026)
This study examines the implementation of Viva Engage as a digital internal communication platform in supporting an Independence Day corporate event at a multinational energy company. The research is grounded in the increasing need for effective digital communication systems that are able to strengthen employee engagement in organizations with complex structures and diverse workforces. The objective of this study is to analyze how Viva Engage contributes to communication effectiveness, employee participation, and engagement during internal corporate events. A descriptive qualitative approach was applied through participant observation, informal interviews, and documentation of the event processes. The findings indicate that Viva Engage facilitated faster information dissemination, encouraged two-way communication, and enhanced employee involvement before, during, and after the event. Interactive features such as announcements, multimedia content, and engagement tools helped create a sense of belonging and improved organizational connectedness. This study implies that digital platforms are not only operational tools but also strategic instruments for reinforcing organizational culture and sustaining employee engagement in multinational corporate settings.